Desenvolvimento, caracterização e atividade antioxidante de marmelada-de-cachorro (Schum.) - Becker, Fernanda Salamoni (2015)
Alibertia sessilis Schum., also known as marmelada-de-cachorro, is a shrubby species from the Cerrado biome used for food and medicinal purposes. The objective of this work was to study the development of marmelada-decachorro by means of physical and chemical parameters; to physically and chemically characterize the ripe fruit and its fractions peel, pulp and seeds; and evaluate the in vitro antioxidant activity of the fruit using different solvent systems and determination methods. The period between anthesis and abscission of the marmelada-de-cachorro was of 72 days. Period marked by the fruit reaching final size, attractiveness and being fit for consumption, culminating in the highest anthocyanin content in the peel and pulp; high soluble solids and total sugars in the pulp, low acidity and a soft fruit. The fruits showed slightly rounded shape, high number of seeds, with high pulp yield. The fractions peel, pulp and seeds were highlighted due to their high levels of carbohydrates and soluble solid, low acidity, medium fiber content and absence and/or low levels of anti-nutritional factors. Glucose and fructose were the predominant sugars in fruit pulp. The seeds cannot be regarded as sources of essential amino acids, though presenting important fatty acids, such as linoleic and oleic acids, for a healthy diet. The fruit showed intermediate levels of ascorbic acid, anthocyanins and carotenoids when compared to other fruits. Solvent ethanol (90%) and water were the most efficient in extracting total flavonoids and total phenolics, as well as in determining antioxidant activity, in all methods. Oxygen Radical Absorbance Capacity - ORAC and Ferric Reducing Antioxidante Power - FRAP were the trials that showed higher reproducibility of the fruit’s antioxidant activity, presenting higher correlations with the contents of total phenolics and total flavonoids.